A case report of multiple primary malignant tumors: breast cancer and colorectal cancer - Kaicaier, Mirinisa; Liu, Shengjie; Zhang, Yuhan; Hou, Xueping; Wang, Yuying; Aikelaimu, Aisaide; Ma, Liyuan; Jiang, Weihua (Frontiers in Oncology, 2025)
Breast cancer and colorectal cancer are both common malignant tumors worldwide. This report describes a case of multiple primary malignant tumors (MPMT) in a 52-year-old female patient diagnosed successively with right breast triple-negative breast cancer (T2N1M0, stage IIb) and rectal moderately differentiated adenocarcinoma (pT3N0M0, stage IIa). Through a multidisciplinary team (MDT) approach, we developed a treatment strategy involving breast-conserving surgery for the breast cancer followed by laparoscopic radical resection for the rectal cancer. Postoperative sequential therapy comprised TP chemotherapy (albumin-bound paclitaxel plus carboplatin), radiotherapy, and capecitabine. The patient developed Grade IV bone marrow suppression during chemotherapy, which improved after aggressive supportive care. The patient is currently in disease remission. This case highlights the importance of multidisciplinary collaboration, genetic risk assessment, individualized treatment decisions, comprehensive tumor management, and robust supportive care in the diagnosis and treatment of multiple primary malignant tumors, providing valuable insights for managing similar clinical cases.